Proses Pembuatan Peraturan Daerah Pendidikan Kabupaten Tanah Datar: Mengintegrasikan Ketentuan Pendidikan Anak Usia Dini Jalur Nonformal dalam Pasal 47 - Megia Zaharatul Jannah (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
This article discusses the importance of public policy, especially Regional Regulations (Perda) on education, as a strategic instrument to improve the quality and access to education at the regional level. Based on the law of regional autonomy, Perda on education is designed through the stages of understanding the issue, preparing the agenda, formulating policies, harmonization, ratification, implementation, and evaluation. One of the important provisions regulated is Article 47 concerning Non-formal Early Childhood Education which regulates the form of non-formal early childhood education units and learning methods based on playing while learning. This study uses a qualitative descriptive method with primary data from interviews with members of the Tanah Datar DPRD. The results show that the success of the Perda on education is greatly influenced by the active participation of stakeholders, harmonization of regulations with higher laws, effective socialization to the community, and ongoing evaluation, including the implementation of the provisions of Article 47 to ensure its positive impact.